Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To determine the correct equation defining the function [tex]\( h(x) \)[/tex], which is the product of functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex], follow these steps:
1. Recall the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
[tex]\[ f(x) = 4x - 6 \][/tex]
[tex]\[ g(x) = 5x + 9 \][/tex]
2. Form the product [tex]\( h(x) \)[/tex] by multiplying [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
[tex]\[ h(x) = f(x) \cdot g(x) \][/tex]
[tex]\[ h(x) = (4x - 6)(5x + 9) \][/tex]
3. Expand the product using the distributive property (FOIL method):
[tex]\[ h(x) = (4x - 6)(5x + 9) \][/tex]
[tex]\[ = 4x \cdot 5x + 4x \cdot 9 - 6 \cdot 5x - 6 \cdot 9 \][/tex]
4. Calculate each term individually:
[tex]\[ 4x \cdot 5x = 20x^2 \][/tex]
[tex]\[ 4x \cdot 9 = 36x \][/tex]
[tex]\[ -6 \cdot 5x = -30x \][/tex]
[tex]\[ -6 \cdot 9 = -54 \][/tex]
5. Combine all the terms:
[tex]\[ h(x) = 20x^2 + 36x - 30x - 54 \][/tex]
6. Simplify the expression by combining like terms:
[tex]\[ 36x - 30x = 6x \][/tex]
[tex]\[ h(x) = 20x^2 + 6x - 54 \][/tex]
Thus, the equation that defines [tex]\( h(x) \)[/tex] is:
[tex]\[ h(x) = 20x^2 + 6x - 54 \][/tex]
Among the given choices, the correct answer is:
D. [tex]\( h(x) = 20x^2 + 6x - 54 \)[/tex]
1. Recall the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
[tex]\[ f(x) = 4x - 6 \][/tex]
[tex]\[ g(x) = 5x + 9 \][/tex]
2. Form the product [tex]\( h(x) \)[/tex] by multiplying [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
[tex]\[ h(x) = f(x) \cdot g(x) \][/tex]
[tex]\[ h(x) = (4x - 6)(5x + 9) \][/tex]
3. Expand the product using the distributive property (FOIL method):
[tex]\[ h(x) = (4x - 6)(5x + 9) \][/tex]
[tex]\[ = 4x \cdot 5x + 4x \cdot 9 - 6 \cdot 5x - 6 \cdot 9 \][/tex]
4. Calculate each term individually:
[tex]\[ 4x \cdot 5x = 20x^2 \][/tex]
[tex]\[ 4x \cdot 9 = 36x \][/tex]
[tex]\[ -6 \cdot 5x = -30x \][/tex]
[tex]\[ -6 \cdot 9 = -54 \][/tex]
5. Combine all the terms:
[tex]\[ h(x) = 20x^2 + 36x - 30x - 54 \][/tex]
6. Simplify the expression by combining like terms:
[tex]\[ 36x - 30x = 6x \][/tex]
[tex]\[ h(x) = 20x^2 + 6x - 54 \][/tex]
Thus, the equation that defines [tex]\( h(x) \)[/tex] is:
[tex]\[ h(x) = 20x^2 + 6x - 54 \][/tex]
Among the given choices, the correct answer is:
D. [tex]\( h(x) = 20x^2 + 6x - 54 \)[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.